2022
DOI: 10.1002/rcm.9301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of isotopic fractionation in the CO2‐O2 isotope exchange reaction

Abstract: Rationale: Oxygen isotope exchange between O 2 and CO 2 in the presence of heated platinum (Pt) is an established technique for determining the δ 17 O value of CO 2 . However, there is not yet a consensus on the associated fractionation factors at the steady state. Methods:We determined experimentally the steady-state α 17 and α 18 fractionation factors for Pt-catalyzed CO 2 -O 2 oxygen isotope exchange at temperatures ranging from 500 to 1200 C. For comparison, the theoretical α 18 equilibrium exchange values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
(301 reference statements)
0
3
0
Order By: Relevance
“…The Δ 17 O of CO 2 was determined using the CO 2 –O 2 exchange method ( Barkan et al 2015 ; Adnew et al 2019 ). A detailed description of the CO 2 –O 2 exchange system at Utrecht University is given in Adnew et al (2019 , 2022) . Equal amounts of CO 2 and O 2 were mixed in a quartz reactor containing a platinum sponge catalyst at the bottom and heated at 750 °C for 2 h. After isotope equilibration, the CO 2 was trapped at liquid nitrogen temperature, while the O 2 was collected with 1 pellet of 5 Å molecular sieve (1.6 mm, Sigma-Aldrich, USA) at liquid nitrogen temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Δ 17 O of CO 2 was determined using the CO 2 –O 2 exchange method ( Barkan et al 2015 ; Adnew et al 2019 ). A detailed description of the CO 2 –O 2 exchange system at Utrecht University is given in Adnew et al (2019 , 2022) . Equal amounts of CO 2 and O 2 were mixed in a quartz reactor containing a platinum sponge catalyst at the bottom and heated at 750 °C for 2 h. After isotope equilibration, the CO 2 was trapped at liquid nitrogen temperature, while the O 2 was collected with 1 pellet of 5 Å molecular sieve (1.6 mm, Sigma-Aldrich, USA) at liquid nitrogen temperature.…”
Section: Methodsmentioning
confidence: 99%
“…where δ 17 O = ( 17 R sample − 17 R reference )/ 17 R reference and δ 18 O = ( 18 R sample − 18 R reference )/ 18 R reference . Theoretical considerations suggest that λ varies from 0.5000 to 0.5305 for different mass-dependent isotope fractionation processes, but recent studies have reported λ values even outside this range ( Hayles et al 2017 ; Adnew et al 2022 ; Hayles and Killingsworth 2022 ). Deviations from Equation ( 3 ) are quantified as Δ 17 O, and in this study, we used the linearized definition for Δ 17 O.…”
Section: Theorymentioning
confidence: 99%
“…Ellis and Passey (2023) built upon this methanation‐fluorination technique, but the initial step of their method involves the high‐temperature conversion of the oxygen in the analyzed material, for example, carbonates, to CO. Isotope exchange between CO 2 and O 2 over hot platinum is another established protocol to obtain high‐precision Δ′ 17 O data (Adnew et al., 2022; Mahata et al., 2013). Limitations of these methods are that they are laborious and involve multiple fractionation steps, which can affect the accuracy of the results.…”
Section: Introductionmentioning
confidence: 99%